How does Transformational Leadership Influence Creativity Through Job Satisfaction? - Rizky Kurnia Hidayat; Heru Kurnianto Tjahjono (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
This research examined how transformational leadership affects creativity through job satisfaction. This study focuses on elementary school teachers as the research subject. A total of 10 elementary schools were selected as the population for the study. This study utilized a total sampling technique, involving all the teachers who work in the ten selected elementary schools as the research participants. In this study, 147 questionnaires were distributed, of which 130 questionnaires completed by teachers were considered usable. This study employed the AMOS 22 application program as the analytical tool for conducting Structural Equation Modelling (SEM) analysis. The analysis revealed that transformational leadership did not directly impact creativity. Transformational leadership had a positive and significant effect on job satisfaction. Job satisfaction had a positive and significant effect on creativity. Transformational leadership positively and significantly affected creativity through job satisfaction with a full mediation. The result has practical and meaningful implications for elementary school principals in fostering teachers’ creativity through transformational leadership and job satisfaction.